Natural resistance against infections: focus on COVID-19. Issue 2 (February 2022) - Netea, Mihai G.; Domínguez-Andrés, Jorge; van de Veerdonk, Frank L.; van Crevel, Reinout; Pulendran, Bali; van der Meer, Jos W.M.
Abstract : Not all individuals exposed to a pathogen develop illness: some are naturally resistant whereas others develop an asymptomatic infection. Epidemiological studies suggest that there is similar variability in susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. We propose that natural resistance is part of the disease history in some individuals exposed to this new coronavirus. Epidemiological arguments for natural resistance to SARS-CoV-2 are the lower seropositivity of children compared to adults, studies on closed environments of ships with outbreaks, and prevalence studies in some developing countries. Potential mechanisms of natural resistance include host genetic variants, viral interference, cross-protective natural antibodies, T cell immunity, and highly effective innate immune responses. Better understanding of natural resistance can help to advance preventive and therapeutic measures against infections for improved preparedness against potential future pandemics. Highlights: Natural resistance against pathogens is described for many infections. There is no reason to believe that this might be different for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. There are discrepancies between different SARS-CoV-2 infection models and the seroprevalence of antibodies in the circulation. Differences in morbidity and mortality between countries suggest that genetic and environmental differences may influence host defense against SARS-CoV-2 infection. Studies on children, adults residing in confined environments, and on individuals residing in different geographical locations suggest that natural resistance against SARS-CoV-2 is present in human populations, and may differentially impact on the course of the pandemic in such populations. Crucial for host survival is the balance between resistance mechanisms aiming to eliminate host pathogens and tolerance mechanisms aiming to avoid collateral damage induced by inflammatory processes.